2001
DOI: 10.1074/jbc.m011579200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulation of AMP-activated Protein Kinase on Insulin-like Growth Factor 1- and Epidermal Growth Factor-dependent Extracellular Signal-regulated Kinase Pathway

Abstract: AMP-activated protein kinase (AMPK) is tightly regu-Mammalian AMP-activated protein kinase (AMPK) 1 plays a key role in the regulation of energy homeostasis and is highly conserved among animals, plants, and fungi (reviewed in Refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 50 publications
8
56
0
Order By: Relevance
“…*, p Ͻ 0.05 versus vehicle. factor (27)(28)(29), which cause NO release. We next determined whether endogenous NO increased AMPK activation in HUVECs.…”
Section: No-induced Ampk Activation Is Camkk␤-dependent-mentioning
confidence: 99%
“…*, p Ͻ 0.05 versus vehicle. factor (27)(28)(29), which cause NO release. We next determined whether endogenous NO increased AMPK activation in HUVECs.…”
Section: No-induced Ampk Activation Is Camkk␤-dependent-mentioning
confidence: 99%
“…Consistent with our results, the inhibitory crosstalk between ERK1/2 and AMPK has been published recently. 25,26 AMPK activation by adiponectin suppressed angiotensin II-induced cardiac fibrosis through inhibition of ERK1/2 and activation of peroxisome proliferatoractivated receptor-a (PPAR-a). 25 In NIH-3T3 cells, AICAR-stimulated AMPK activation downregulated IGF-1-or epidermal growth factordependent ERK1/2 pathway and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been shown that S259A-Raf is about 2.5-fold more active than the wild-type molecule (30), an effect that is sufficient to increase the expression of SM-MHC in VSM cells (18). Similarly, activation of endogenous Raf by stimulating receptor tyrosine kinases with IGF, epidermal growth factor, or NGF revealed an about 2-3-fold activation of the Raf kinase activity (44,45). In PDGFstimulated VSM cells, PI 3-kinase inhibition increased the late-phase Raf activity by about 2-fold, an effect that was sufficient to generate a prolonged ERK1/2 phosphorylation.…”
Section: Fig 6 Pi 3-kinase Inhibition Augments the Pdgf-induced Latmentioning
confidence: 99%